Disparate effects of adalimumab and fumaric acid esters on cardiovascular risk factors in psoriasis patients: results from a prospective, randomized, observer‐blinded head‐to‐head trial. (2nd July 2020) - Holzer, G.; Hoke, M.; Sabeti‐Sandor, S.; Perkmann, T.; Rauscher, A.; Strassegger, B.; Radakovic, S.; Tanew, A.
Abstract: Background: The effect of adalimumab and fumaric acid esters (FAE) on the cardiovascular risk associated with psoriasis has only been investigated scarcely in randomized controlled studies. Objective: The aim of this prospective, randomized controlled head‐to‐head trial was to compare the influence of adalimumab and FAE on cardiovascular disease markers in psoriasis patients. Methods: Sixty‐five patients with moderate to severe plaque psoriasis were randomly assigned to adalimumab or FAE treatment for 6 months. Cardiovascular haemodynamic parameters [flow‐mediated dilation (FMD), nitro‐glycerine mediated dilation (NMD) and carotid intima–media thickness (CIMT), blood pressure] were assessed at baseline (v0) and after 6 months (v6). Cutaneous disease severity, inflammatory and lipid cardiovascular risk markers were analysed at baseline(v0), after 3 (v3) and 6 months (v6). Results: After 6 months of treatment FMD in the adalimumab group increased significantly [v0 5.9% (6.4% SD), v6 8.0% (4.8% SD), P  = 0.048) but not in the FAE group. (v0 7.0% (4.1% SD), v6 8.4% (6.1% SD), P  = 0.753]. This was paralleled by a significant decrease of high sensitive C‐reactive protein (hsCRP) in the adalimumab group in comparison to the FAE group (v0: 0.39 mg/dL (0.38 SD), v6: 0.39 mg/dL (0.48 SD), P  = 0.043). No significant changes were observed in any other haemodynamic parameters. FAE, however, additionally decreased total cholesterol ( P  = 0.046) and apolipoprotein B ( P  = 0.041) levels compared to adalimumab. Mean Psoriasis Area and Severity Index (psoriasis area severity score) reduction was greater but not significant ( P  = 0.116) under adalimumab treatment compared to FAE treatment [−71.1% (29.9 SD) vs. −54.6% (45.7%)]. Conclusion: In our study, both treatments were documented to exert effects on the cardiovascular system. While adalimumab showed anti‐inflammatory effects and improved FMD, FAE interacted favourably with the cholesterol metabolism.